Corporate Social Responsibility Disclosure and Cost Equity Capital in Industrial Product Industry - Mohd Waliuddin, Mohd Razali; Wong, Yik Fui; Shazali, Shaharuddin; Akmal Hisham, Tak; Mohd Uzairi, Ahmad Hajazi (ICOHLCB, 2017)
Corporate Social Responsibility (CSR) disclosure is now becoming an increasingly popular topic of discussion. Through a strategic approach to CSR, companies are able to boost its competitiveness while gaining other benefits from risk management, reducing cost, and better access to capital, innovation and development. The main objective of the study is to investigate the CSR disclosure by companies listed under industrial product industry toward cost of equity capital. The CSR disclosure score is measured by the extent of CSR disclosure in the annual report. A total of 59 samples of annual reports of listed companies for the periods 2012 to 2014 were obtained and examined. After accounting for control variables such as company size, liquidity, and board independence, the regression results showed CSR disclosure, and other control variables such as liquidity, and board independence had negative relationship with cost of equity capital. However, only company size has positive relationship with the cost of equity capital. The results revealed that the CSR disclosure in the annual reports reduces the cost of equity capital by reducing the information asymmetry and thereby reducing the companies’ risk. For future research, this paper recommends the study be expanded by using other CSR index and measurement of cost of equity.